Rancang Bangun Sistem Informasi Penjualan Alat Tulis Kantor Menggunakan Metode Payment Gateway dan Cash On Delivery - Febriani Lolo Keke; Andreas Ariyanto Rangga; Agustina Purnami Setiawi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Technological developments are increasingly rapid, as evidenced by the large number of individuals and businesses from various industries who depend on computers to support their daily operations, as well as the small, medium and medium sectors. Large companies that already manage payroll processing tasks every month certainly require the use of computers so that the process can function properly. It is hoped that the web-based stationery sales information system at Istana Anugerah can stimulate public interest in purchasing the shop's merchandise. This information system is expected to facilitate consumers' ability to place orders from any location without having to physically visit the store, as well as facilitating the sales department's ability to produce sales reports more quickly and without errors.